2007
DOI: 10.1080/00048670701213245
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Brodmann's Area 46 from Subjects with Schizophrenia

Abstract: The present study has identified genes that are differentially expressed in BA 46 in schizophrenia. Initial studies have shown that there is a need for a careful validation of genes shown to be affected in schizophrenia using high-throughput technologies. In addition the present study has shown that gene expression may vary considerably depending on the duration of schizophrenia. This raises the hypothesis that changing gene expression may be underlying the change in symptom profile that occurs with disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 56 publications
5
54
2
Order By: Relevance
“…In our study, we found that two housekeeper genes β-Actin and GADPH mRNAs which do not differ between people with schizophrenia compared to control as previously found ( [58], [59]) and our data suggests that both are particularly stable mRNAs and useful housekeeping control genes for our postmortem human brain studies. However, if should be emphasized that the utility of GADPH as a control varies from brain collection to brain collection as some laboratories find GADPH to be stable and to not differ in people with schizophrenia as compared to controls as we do ( [60], [59]), while others suggest that is one of the least stable and thus least reliable control genes ( [22], [61]).…”
Section: Discussionsupporting
confidence: 84%
“…In our study, we found that two housekeeper genes β-Actin and GADPH mRNAs which do not differ between people with schizophrenia compared to control as previously found ( [58], [59]) and our data suggests that both are particularly stable mRNAs and useful housekeeping control genes for our postmortem human brain studies. However, if should be emphasized that the utility of GADPH as a control varies from brain collection to brain collection as some laboratories find GADPH to be stable and to not differ in people with schizophrenia as compared to controls as we do ( [60], [59]), while others suggest that is one of the least stable and thus least reliable control genes ( [22], [61]).…”
Section: Discussionsupporting
confidence: 84%
“…However, the mechanism by which DISC1 contributes to the pathophysiology of schizophrenia remains unknown. Although reduced expression of DISC1 mRNA was found in lymphoblastoid cell lines of family members with the translocation (26) and in bipolar disorder patients with a putative risk-associated haplotype (27), no changes were detected in the brain tissue of unrelated patients with schizophrenia or in individuals carrying risk-associated genotypes (28)(29)(30). The evidence from a variety of studies in cell and animal models as well as in human brain tissue suggests that DISC1 mRNA and/or protein processing is complex, and it therefore is plausible that changes in gene processing occur in patients who have major mental illness (28,(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 88%
“…We were particularly interested in CNTNAP2 and PCDH17, because variation in CNTNAP2 has been linked to language and autism spectrum disorders (29,30), and PCDH17 expression was recently suggested to be increased in the prefrontal cortex in a cohort of schizophrenic subjects (31). In sharp contrast to the regionally restricted distribution observed for human CNTNAP2, expression in the developing mouse brain was broad (Fig.…”
Section: In Situ Hybridization Highlights Regionally Restricted Exprementioning
confidence: 99%